PEMBELAJARAN BERDIFERENSIASI DENGAN MEMANFAATKAN MULTIMEDIA PADA PEMBELAJARAN PAI DI SMP IT NURUL ILMI - Abda Daulay, Aslamiyah; Darlis, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract This study aims to analyze differentiated learning by utilizing multimedia in the Islamic Religious Education (PAI) learning process at SMP IT Nurul Ilmi. This research uses a descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation of the learning process. Data analysis techniques were carried out descriptively and qualitatively through data reduction, narrative data presentation, and drawing conclusions based on research objectives. The results of the study show that differentiated learning integrated with multimedia has a positive impact on increasing student participation and understanding. Teachers are able to organize a variety of learning activities, such as interest-based group discussions, creative projects, and digital quiz-based practice questions such as Quizizz. Limited devices and low digital literacy among students are the main challenges that hinder the learning process. In general, this approach has been proven to increase learning motivation and build students' spiritual understanding in a deeper and more contextual way. As a recommendation for further research, it is necessary to explore the effectiveness of multimedia-based differentiated learning at various levels of education and other subjects.